Education of legal human as way to the construction of law governed society in contemporary Ukraine - Сліпенчук, В. О. (Problems of legality, 2015)
The article is devoted to the study of the process of legal education of the individual, the impact on the formation of legal consciousness. Analyzed understanding of the educational process and its possibilities in the concept of philosophy of education S.I. Hessen. Defined the main directions of education legal human in Ukrainian society.